Cattle manure quality in Maragua District, central Kenya: Effect of management practices and development of simple methods of assessment - Lekasi, J.K.; Tanner, J.C.; Kimani, S.K.; Harris, P.J.C. (Elsevier, 2003)
Three hundred mixed, smallholder farms in Kariti location, Kandara Division, Maragua District, Central Kenya, were surveyed. Dairy cattle management practices, including type of animal enclosure, roofing, floor type, drainage, use of bedding, feeding of concentrates; and manure management practices, including methods of manure handling and storage prior to utilization, and the addition of urine and organic materials to manure were documented. The concentrations of C, N, P, K, Ca, and Mg, and the C:N ratio of manure-composts prepared on-farm were analysed. The P concentration of manure was higher from zero-grazing units than from improved or traditional housing, higher from housing with roofs than from that without, higher when animals were fed concentrates than when not, and higher when manure was stored in a heap or pit rather than in a deep littering system. Use of bedding in the livestock housing resulted in manure with lower mineral N concentration and higher C:N ratio. Turning manure during composting resulted in manure with a higher mineral N concentration and lower C:N ratio. Results suggest that modification of traditional livestock housing (boma) to the zero-grazing system may have beneficial effects on some aspects of manure quality. Data on manure texture, colour, smell and biological activity were collected in an attempt to relate manure nutrient concentration and C:N ratio to easily discernible characteristics of manure-composts on-farm. Significant relationships were found between manure texture and the concentrations of P and mineral N, and C:N ratio. Significant relationships were also found between manure colour and N concentration and between manure age and mineral N concentration. Thus, there is scope for the development of decision tools to predict manure-compost quality from at least some manure characteristics. Dichotomous keys were prepared to determine mean manure C:N ratio and mineral N concentration on the basis of manure age and texture.